Application of Contextual Teaching and Learning (CTL) Learning Strategies on Metacognitive Ability and Leaarning Outcomes in Immune System Materials - Safrida Safrida; Muhibuddin Muhibuddin; Maulinda Yani (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to determine the differences in metacognitive abilities and student learning outcomes after applying Contextual Teaching and Learning (CTL) learning strategies in the experimental class and the control class on the material of the immune system. The research method used is an experimental method with a pretest-posttest control group research design. The research subjects were 125 students at SMAN 2 Lhokseumawe. The parameters measured were metacognitive ability using a questionnaire and learning outcomes using the multiple-choice type test objective. Data was collected through pretest and posttest on metacognitive abilities, and learning outcomes were analyzed by parametric statistical tests using independent sample t-test. The metacognitive t-test on the score strongly agrees with the students in the experimental class and the control class, namely tcount (6.14) > ttable (1.65) significantly different. Metacognitive t-test on scores quite agrees with students in the experimental class and control class, namely tcount (0.61) < ttable (1.65) not significantly different. The metacognitive t-test on the score slightly agrees with the students in the experimental class and the control class, namely tcount (10.07) > ttable (1.65) significantly different. The metacognitive t-test on the students' disagreeing scores in the experimental class and control class, namely tcount (14.40) > ttable (1.65), was significantly different. The results showed differences in the application of CTL learning strategies to metacognitive abilities and learning outcomes between the experimental and control classes. It can be concluded that there are differences in metacognitive abilities and learning outcomes between the experimental class and the control class after the application of the CTL learning strategy to students at SMAN 2 Lhokseumawe on the subject of the immune system